Implementation of supervised exercise therapy in a veteran population with symptomatic claudication. (April 2022) - Elissa Altin, S; Schneider, Marabel D; Parise, Helen; Banerjee, Subhash; Wu, Wen-Chih; Meadows, Judith L; Pfau, Steven; Keefe, Heidi; Armstrong, Ehrin J
Background: Real-world implementation of supervised exercise therapy (SET) referral for symptomatic intermittent claudication has been limited by poor provider awareness around reimbursement and low patient adherence owing to factors including limited center availability and long travel distances to sites. Methods: In this study, 76 of 77 consecutive male veteran patients with intermittent claudication managed at a single-center vascular specialty clinic were referred to SET prior to revascularization. Pre- and post-SET submaximal exercise treadmill testing was performed for assessment of exercise capacity in metabolic equivalents (METs). Results: In the 48.7% of subjects who completed 36 sessions of SET ( n = 37), the average improvement in METs was 60.3%, reflecting improvement from baseline average of 3.4 METs to 5.5 METs after SET. Another 14 patients pursued self-guided exercise therapy and 25 patients declined any participation in exercise therapy. Reasons for declining participation in SET included inadequate transportation, cost of copayment, and interference with full-time work schedules. There was a nonsignificant numeric trend toward improved change in ankle–brachial index in the combined SET and self-guided exercise groups compared to those that declined exercise therapy (0.011 ± 0.124 vs –0.040 ± 0.105, p = 0.156). Conclusion: High acceptance of referral to SET is possible, despite the limitations to implementation. Incorporation of novel pre- and post-SET submaximal exercise treadmill testing allows for assessment of change in exercise capacity and aids in risk stratification and management of intermittent claudication symptoms.